Characterization of Spontaneous Malignant Lymphomas in Japanese Macaques (Macaca fuscata). (May 2015) - Hirata, A.; Hashimoto, K.; Katoh, Y.; Sakai, H.; Bruce, A. G.; Rose, T. M.; Kaneko, A.; Suzuki, J.; Nikami, H.; Yanai, T.
Lymphomas are common spontaneous tumors in nonhuman primates but remain poorly characterized in Japanese macaques ( Macaca fuscata ). This study examined 5 cases of spontaneous malignant lymphoma in Japanese macaques, focusing on the immunophenotypes and presence of simian lymphocryptoviruses, which are Epstein-Barr virus-related herpesviruses in nonhuman primates. The macaques with lymphoma were 5 to 28 years old, indicating that lymphomas develop over a wide age range. The common macroscopic findings were splenomegaly and enlargement of lymph nodes. Histologic and immunohistochemical analyses revealed that all cases were non-Hodgkin type and exhibited a T-cell phenotype, positive for CD3 but negative for CD20 and CD79α. The lymphomas exhibited diverse cellular morphologies and were subdivided into 3 types according to the World Health Organization classification. These included 3 cases of peripheral T-cell lymphoma, not otherwise specified; 1 case of T-cell prolymphocytic leukemia; and 1 case of an unclassifiable T-cell lymphoma. Positive signals were detected by in situ hybridization in 2 of the 4 examined cases using probes for the Epstein-Barr virus-encoded small RNA (EBER). Furthermore, the presence of M. fuscata lymphocryptovirus 2, a macaque homolog of Epstein-Barr virus, was demonstrated in EBER-positive cases by polymerase chain reaction amplification followed by direct sequencing. Immunohistochemistry using antibody to the Epstein-Barr virus-encoded nuclear antigen 2 was negative, even in the EBER-positive cases. The present study suggests that T-cell lymphoma is more common than B-cell lymphoma in Japanese macaques and that M. fuscata lymphocryptovirus 2 is present in some cases.